Effect of thread material and stitch orientation on tensile mechanical property of stitched oil palm empty fruit bunch fiber reinforced epoxy composites - Ahamd Ghazilan, Ahmad Luqman; Mokhtar, Hanan; Shaik Dawood, Mohd. Sultan Ibrahim (Zes Rokman Resources, 2016)
Short random fibers do not have the desired mechanical performance as continuous fibers, but this weakness may be overcome by applying methods that make up for their deficiency. Stitching is one of the methods that have been proven to be an effective reinforcement for through-thickness (out-of-plane) mechanical properties by incorporating z-direction reinforcements of synthetic fiber. There are not many studies on stitch thread effect on the mechanical performance of bio composites, thus the effect of thread material and stitch row orientations on the tensile strength and modulus of elasticity are investigated. Tensile tests were performed in accordance to ASTM D 638 specifications using Universal Testing Machine INSTRON 5582. The data indicates that incorporating thread material of Nylon 210D improves the tensile performance due to the additional load bearing capability and better surface interfacial adhesion on the outer ply of stitched thread with epoxy resin. The results also indicate that by incorporating parallel stitch row orientation, the oil palm empty fruit bunch fiber reinforced epoxy composite’s tensile performance improves due to the increase in fiber volumetric content for load bearing conditions from additional stitched threads. Therefore, it was found that the material thread and stitch row orientation affect the tensile performance, and that using Nylon 210D and parallel stitch row orientation optimizes the tensile performance of stitched palm oil empty fruit bunch fiber reinforced epoxy composites.